Effect of carboxymethyl cellulose and/or wheat gluten on the pasting, rheological and quality properties of wheat starch-based batter for deep-fried products - Ying Xu; Ruishu Zhang; Kangyu Wang; Prince Chisoro; Feng Huang; Jing Wang; Chunhui Zhang (Food Chemistry: X)
This study aimed to investigate the effects of the individual and synergistic addition of wheat gluten (WG) and carboxymethyl cellulose (CMC) on the wheat starch (WS)-based batter characteristics to determine the molecular basis of texture formation in the actual batter system. Results showed that adding WG and/or CMC significantly increased the viscosity of WS during pasting. The rheological behavior showed that the WG-treated and CMC-treated group had the highest and lowest viscoelasticity. The addition of WG-CMC helped the WS-based batter obtain moderate viscoelasticity. These outcomes could be attributed to the enhancement of hydrogen bonding. The microstructure suggested that the addition of WG-CMC increased the density and integrity of the gel network. Overall, CMC competed for the binding sites of WG on WS, reducing the increase in viscoelasticity caused by the interaction between WG and WS. This might alleviate the unwanted springiness of fried products.